Global trends in the burden of alcohol use disorders in the working-age population from 1990 to 2021 and projections for the next 20 years - Xinyu Cui; Xinyu Cui; Kexin Liu; Yuanyi Ji; Su Han; Yongzhong Cheng (Frontiers in Public Health, 2025)
IntroductionAlcohol use disorders (AUD) have long been among the most disabling mental disorders and a leading cause of health loss. However, data on the burden and trends of these disorders among the working-age population are scarce.MethodsThis study aimed to assess trends in the burden of AUD among people aged 15-64 years from 1990 to 2021 at the global, regional and national levels and to project future trends. Based on the trend analysis of the Global Burden of Disease Study 2021 (GBD2021), we report age-standardized data and estimated annual percentage changes (EAPC) for the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of AUD in the working-age population at the global, regional, and national levels and analyze global trends by age, sex, and social development index (SDI). Furthermore, critical inflection points and local trends Average Annual Percent Change (AAPC) were further explored via joinpoint regression analysis, and the burden of AUD was predicted via the Bayesian age-period-cohort (BAPC) model.ResultsGlobally, the incidence number of AUD cases among people aged 15-64 years in 2021 was estimated to be 51340.37 × 103 (95%UI 37577.93 × 103 −68135.93 × 103). During the period from 1990 to 2021,the age-standardized incidence rate (ASIR) (EAPC = −0.85, 95%CI: −0.89 to −0.81, p < 0.05), age-standardized mortality rate(ASMR) (EAPC = −1.98, 95%CI: −2.43 to −1.54, p < 0.05) and age-standardized disability-adjusted life year (DALY) rate (ASDR) (EAPC = −1.39, 95%CI: −1.59 to −1.19, p < 0.05) decreased significantly. In terms of regions, from 1990 to 2021, the disease burden in areas with a medium--to-high socio-demographic index (SDI) was greater, and this trend was particularly pronounced in Eastern Europe.Disease burden and SDI level showed a trend of stage correlation, ASDR (R = 0.28, p < 0.001). At the national level, the country with the highest disease burden was Mongolia,the prevalence rate in 2021 will be 7087.13 cases per 100,000 (95% UI:5192.08 to 9339.88), while Mongolia leads in terms of DALYs and mortality rates. It is estimated that by 2044, the global ASPR and ASDR will reach 766.67/100,000 and 205.88/100,000, respectively.DiscussionDespite the decline in AUD among the working population over the past 30 years, significant differences remain between genders,regions and ages, and these differences continue to have important public health consequences. In the face of diverse interests and the reality of global health inequalities, strategies to prevent and reduce the burden of disease still require sustained efforts. Over the past 30 years, AUD have seen a notable decline. The passage of the 2022-2030 Global Alcohol Action Plan marks a pivotal moment in global policy formulation. Despite the various interests and the reality of global health inequalities, these disparities continue to yield significant public health consequences. Efforts to minimize the health losses caused by alcohol consumption and prioritize interventions targeting labor populations are particularly important.